Pendidikan Spiritual untuk Rehabilitasi Korban Penyalahgunaan Narkoba di Pondok Pesantren Darul Iman Paguyangan – Brebes : Spiritual Education for the Rehabilitation of Drug Abuse Victims at Darul Iman Islamic Boarding School Paguyangan - Brebes - Moh. Wahyudin (CV. Kalimasada Group, 2023)
Spiritual education is experiences that are carried out consciously to direct the soul to keep going according to its nature, namely to believe in Him and develop Divine potential until the culmination of faith in God, so that his soul can encourage physical activity or daily actions to always walk in accordance with Islamic law. Someone who lacks spiritual education is easier to do juvenile delinquency. Juvenile delinquency is an act of doing some of the teenagers that is contrary to the law, religion and norms of society so that the consequences can harm others, disrupt public tranquility and also damage themselves. So that parents are expected to provide religious education in their families, because the education that was first received by a child is education in the home. As parents, they must set a good example for their children, because children will imitate what they see and hear.